Modernisasi Kelembagaan Partai Politik Studi Kasus Partai Gerindra Jawa Tengah - Sugiarto Sugiarto; Teguh Yuwono (Universitas Medan Area, 2021)
The Institutional Modernization of the Central Java Gerindra Party is interesting to study because the Gerindra Party is a new party that has a significant voting trend in Central Java, after PDIP. The objective of this study is to describe institutional modernization in Gerindra Party of Central Java and to analyze the obstacles to modernization within the Central Java Gerindra Party. The research method used was a qualitative method with descriptive analysis. The location of this research was the scope of the Central Java Gerindra Party DPD and the Central Java Gerindra Party wing. The research design used a descriptive research design with a qualitative approach. Data collection techniques used in-depth interviews and documentation. The informants consisted of the Chairperson of the Central Java Party DPD, Deputy Chair of the Central Java Party DPD, Secretary General of the Central Java Gerindra Party DPD, Chair of the Organization, Membership and Cadreization, Chair of the Women's Division, Chair of the Empowerment of Sayap Organizations, Members of Sayap (Indonesia Raya Gerindra Volunteer Unit) SATRIA Gerindra Voters or supporters of Gerindra Party. Gerindra Party has experienced modernization in the areas of access to open information and financial transparency, application of a democratic ideology, gradual regeneration, and preparation for leadership rotation through the party regeneration process. The institutional modernization of Gerindra Party was still hampered by the lack of respect for female cadres and the personalization of Gerindra figures who were only focused on certain people.